Tradition und Zukunft - die Niedersächsische Staats- und Universitätsbibliothek Göttingen - eine Leistungsbilanz zum 65. Geburtstag von Elmar Mittler - Bargheer, Margo; Ceynowa, Klaus (Universitätsverlag Göttingen, 2005)
This book assembles like a balance of activities papers about all working areas of the Lower Saxony State and University Library (SUB), forming a Festschrift for its director Elmar Mittler for his 65 birthday. Within the library is shown as an absolutely consequent service oriented supplier to the Georg-August-University as well as center of innovation to the German and international library community.